Implementasi Kebijakan Pemerintah Dalam Pemenuhan Hak-hak Pendidikan Penyandang Disabilitas di Kecamatan Dau - Nada, Fairoh Aida Qothrun; Cikusin, Yaqub; Sunariyanto, Sunariyanto (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The purpose of this paper is to describe and analyze the implementation of government policy in fulfilling the educational rights of persons with disabilities in Dau District and explain the factors that influence the implementation of government policy in fulfilling the educational rights of persons with disabilities in Dau District. This research uses descriptive qualitative research methods which are used in this research to obtain information regarding the process of implementing government policies in fulfilling the educational rights of people with disabilities in Dau District. Data collection methods through observation, interviews and documentation. Data analysis techniques starting from data collection, data presentation, data reduction, and verification. The results of this research show that the factors that influence policy implementation are a form of conservation of the fulfillment of the educational rights of people with disabilities. The human resource factor is one of the influencing factors where the availability of subject teachers has not been followed by the ability of the teachers to provide special treatment for children with special needs during the teaching and learning process, this is because none of the subject teachers have a background in Special Education. (PLB), so it still requires adaptation, both patience and ability in the learning process. As well as financial resources (Budget) in the policy of fulfilling the rights of persons with disabilities in the field of education are still not adequately met.